Screening for probiotic properties and potential immunogenic effects of lactobacilli strains isolated from various food products - Kowalczyk, Magdalena; Radziwill-Bienkowska, Joanna M.; Marć, Małgorzata A.; Jastrząb, Rafał; Mytych, Jennifer; Siedlecki, Paweł; Szczepankowska, Agnieszka K. (Frontiers in Microbiology, 2024)
Deceleration of disease progression and re-establishment of microbial balance in the gut is often achieved by application of lactobacilli strains. Their beneficial effects are associated with probiotic properties, which may be accompanied by immunomodulatory action at mucosal surfaces. To single out such strains, we screened three hundred lactobacilli isolates from eight genera and various food sources. Examination of acid and bile salt tolerance as well as adhesion to mucin, allowed for selection of forty strains with probiotic potential. Based on hemolytic and antibiotic susceptibility studies, we determined that thirty-five among the forty strains exhibit biosafety features warranting future applications. Using an in vitro cell line model, we showed that the cell-free supernatant (CFS) fractions of five lactobacilli strains exert differentiating immunomodulatory effects. CFS from Lactiplantibacillus L_4 strain downregulated proinflammatory cytokines IL-8 and IL-1β, while from Lactiplantibacillus L_2 and L_5 increased IL-8 levels and from Lacticaseibacillus L_1 and Lactiplantibacillus L_3 upregulated IL-1β levels. Overall, our result delineate a rational approach of selecting lactobacilli strains for probiotic development to support the gut microbiota equilibrium and reinforce the host immune system.